Effect of ball speed during soccer heading on concussion assessment scores - Hoogeveen, A. M.; Tierney, R. T.; McDevitt, J. K.; Dorminy, M. L.; Higgins, M. (Journal of Athletic Training, 2013)
Due to the increasing popularity of soccer in the US, the numbers of brain injury due to repetitive head impact have also increased. Certified athletic trainers have used sideline concussion tests to indicate whether or not an athlete has impairments that can be indicative of a concussion. Soccer heading ball speeds may influence injury risk, but have not been evaluated in a controlled, yet functional, setting. Objective: To determine the influence of soccer heading ball speed on concussion sideline assessment scores. Design: Pre-test post-test repeated measures research design. Setting: Athletic training laboratory and gymnasium. Participants: Sixteen current division one collegiate soccer players (age= 20.4 ± .96; M = 10; F = 6) with no history of head or neck injury in 6 months prior to testing, no braces on their teeth, and at least 5 years of soccer heading experience participated. Intervention: The independent variables were ball speed (30, 40, and 50mph; randomized) and time (pretest vs. posttest). Ball speed was a between-subjects factor (30mph n = 5, 40mph n = 5, 50mph n = 6) and time was a repeated-measure. Soccer balls were projected from a JUGS soccer machine at 30, 40 and 50 mph. Subjects performed at least 5 standing headers at their respective ball speeds. Concussion assessments were performed approximately 1 week prior to and immediately post soccer headings. Main Outcome Measures: Sideline concussion assessments included the Standard Concussion Assessment Tool 2 (SCAT2), Balance Error Scoring System Score (BESS), and King Devick Test (KDT). Group (3) by time (2) MANOVAs and ANOVAs with repeated measures on time were performed using SPSS v19, p < .05. Results: There were no statistically significant differences between ball speed groups on any concussion assessment measures over time. There was a statistically significant main effect, F(1,13) = 9.08, p = .010, in KDT for time where the posttest KDT time (37.6 + 6.8 sec) was lower than the pretest (40.0 + 5.1 sec). Slight symptoms (1 of 6 severity endorsed), such as headache, pressure in the head, neck pain, and fatigue, were elicited post-heading in some players during the SCAT2 evaluation. Conclusions: Heading a soccer ball at 30, 40, 50 mph did not cause statistically significant increases in concussion assessment scores. The KDT significant result in overall time could be attributed to a learning effect. Although no statistically significant results were identified in the concussion assessments over time, slight symptoms were elicited in some players post heading. These transient slight symptoms following high-speed head impacts in sports are common, but their significance is not well understood. Sports medicine health care professionals need to remain proactive and conservative in their concussion management strategies.